Simple attributes predict the value of plants as hosts to fungal and arthropod communities - Bruun, Hans Henrik; Brunbjerg, Ane Kirstine; Fløjgaard, Camilla; Dalby, Lars; Frøslev, Tobias Guldberg; Haarder, Simon; Heilmann-Clausen, Jacob; Hoye, Toke; Læssøe, Thomas; Ejrnæs, Rasmus (Dryad, 2022)
Fungal and arthropod consumers constitute the vast majority of global
terrestrial biodiversity. Yet, the link from richness and composition of
producer (plant) communities to the richness of consumer communities is
poorly understood. Fungal and arthropod species richness could be a simple
function of producer species richness at a site. Alternatively, it could
be a complex function of chemical and structural properties of the
producer species making up communities. We used databases on plant-fungus
and plant-arthropod trophic links to derive the richness of consumer biota
per associated plant species (coined link score). We assessed how well
link scores could be predicted by simple attributes of plant species.
Next, we used a multi-taxon inventory of 130 sites, representing all major
habitat types in a country (Denmark), to investigate whether link scores
summed over plant species in communities (coined link sum) could
outperform simple plant species richness as predictor of fungal and
arthropod richness at the sites. We found plant species’ link scores for
both fungi and arthropods to be positively related to plant size, regional
occupancy, nativeness and ectomycorrhizal status. Link-based indices
generally improved the prediction of richness of fungal and arthropod
communities. For fungal communities, both observed link sum (from
databases) and predicted link sum (from plant attributes) had high
predictive power, while plant richness alone had none. For arthropod
communities, predictive performance varied between functional groups. For
both fungi and arthropods, richness predictions were further improved by
considering abiotic habitat conditions. Our results underline the
importance of plants as niche space for the megadiverse groups of
arthropods and fungi. The plant-attribute approach holds promise for
predicting local and regional consumer richness in areas of the world
lacking detailed plant-consumer databases.
Data on plant-fungus and plant-arthropod interaction links for the 549
plant species found across the 130 BioWide sites in Denmark. Detailed
descriptions of field data collection protocols are found in Brunbjerg AK,
Bruun HH, Brøndum L, Classen AT, Dalby L, Fog K, et al. (2019) A
systematic survey of regional multi-taxon biodiversity: evaluating
strategies and coverage. BMC Ecology 19(1):43. doi:
10.1186/s12898-019-0260-x. Raw data on known interaction links between all
relevant plant taxa (1349 taxa on the species or genus levels) and
associated arthropod species were retrieved from the BRC database
(https://www.brc.ac.uk/dbif/) and similar data regarding associated fungal
species from the Danish Fungal Database (https://svampe.databasen.org/).
The raw data were processed to obtain an observed arthropod link score and
an observed fungal link score per plant species. The calculus of link
scores from raw data is detailed in the associated manuscript. Attributes
of the 549 plant species used to model their predicted link score
(ectomycorrhizal status, native area, occupancy in Denmark, phylogenetic
grouping, lifespan, life form and size) were compiled from sources
detailed in the associated manuscript.
This archive includes the R code and formatted data used in the associated
manuscript. It may be used to reproduce the figures and tables.
Keywords: Trophic interactions; plant traits; mycorrhizal fungi; phytophagous arthropods; Ecospace; multi-taxon biodiversity; FOS: Biological sciences